Factors Affecting Customer Interest in Opening Wadi’ah Saving Accounts at Bank Syariah Indonesia - Yari Indra Mega Aryani; Mairijani (P3M Politeknik Negeri Banjarmasin, 2024)
The adoption rate of wadiah savings still requires special attention. This research aimed to fill the gap of former researches (Yuliawati and Asmar) that revealed the interest of saving in sharia banking hasn’t influenced by variables of religiosity, literacy on sharia finance and Islamic branding. This research used a descriptive quantitative method by collecting primary data through distributing questionnaires to Bank Syariah Indonesia customers in Banjarmasin City (100 samples). Data analysis process is carried out to evaluate the influence of religiosity, financial literacy, company performance, and trust factors on customer interest in opening a wadiah savings account. The results showed that all the factors such as religiosity, financial literacy, company performance, and trust had a significant influence on customer interest. The religiosity and trust factors show the strongest influence, followed by financial literacy and company performance. These findings emphasize the importance of strengthening religiosity and trust factors in Bank Syariah Indonesia’s marketing strategy to increase customer participation in Islamic savings products.